A cytochrome b561 with ferric reductase activity from the parasitic blood fluke, Schistosoma japonicum. - Amber Glanfield; Donald P McManus; Danielle J Smyth; Erica M Lovas; Alex Loukas; Geoffrey N Gobert; Malcolm K Jones (Public Library of Science (PLoS), 2010)
BACKGROUND: Iron has an integral role in numerous cellular reactions and is required by virtually all organisms. In physiological conditions, iron is abundant in a largely insoluble ferric state. Ferric reductases are an essential component of iron uptake by cells, reducing iron to the soluble ferrous form. Cytochromes b561 (cyts-b561) are a family of ascorbate reducing transmembrane proteins found in most eukaryotic cells. The identification of the ferric reductase duodenal cytochrome b (dcytb) and recent observations that other cyts-b561 may be involved in iron metabolism have opened novel perspectives for elucidating their physiological function. METHODOLOGY/PRINCIPAL FINDINGS: Here we have identified a new member of the cytochrome b561 (Sjcytb561) family in the pathogenic blood fluke Schistosoma japonicum that localises to the outer surface of this parasitic trematode. Heterologous expression of recombinant Sjcyt-b561 in a Saccharomyces cerevisiae mutant strain that lacks plasma membrane ferrireductase activity demonstrated that the molecule could rescue ferric reductase activity in the yeast. SIGNIFICANCE/CONCLUSIONS: This finding of a new member of the cytochrome b561 family further supports the notion that a ferric reductase function is likely for other members of this protein family. Additionally, the localisation of Sjcytb561 in the surface epithelium of these blood-dwelling schistosomes contributes further to our knowledge concerning nutrient acquisition in these parasites and may provide novel targets for therapeutic intervention.